Navigating Citizenship in the Harbour City: Sexuality, ethnicity and belonging among Lebanese, Indian and Anglo LGBTQ+ young adults in Sydney, Australia - Kumar, Sujith (UNSW Sydney, 2021)
Drawing on Karen Barad’s agential realism and the lens of citizenship, this thesis explores the lived experiences and attitudes of Lebanese, Indian and Anglo LGBTQ+ young adults living in Sydney, Australia. Data collection and analysis were based on qualitative in-depth narrative interviews (n=42) and optional follow-up photo-elicitation interviews (n=20). Participants’ responses, analysed abductively, were framed along broader themes of moral, cultural and sexual citizenship, each further contextualised using aspects of Barad’s theorising: diffraction, time and agency. The thesis has three main findings. First, ‘Australianness’ was predicated on a form of Whiteness that is linked to colonial history and disenfranchisement of First Nations peoples, with consequences for social participation, inclusion within LGBTQ+ communities, and sexual citizenship. Second, heteropatriarchal community values, material culture, religion and spatiotemporal geographies were found to be key factors that influenced young adults’ connection with their cultural communities. Third, the attainment of – or limits to – sexual citizenship and participation was found to be a collaborative endeavour created by an entanglement of formal and informal policies, everyday experiences and material factors. While intersections along the lines of ethnicity, gender, financial ability, locality, disability and so on influenced participants’ participation in domains of everyday life, employing a Baradian framework revealed that young people were far from passive subjects in their social environments and often found ways to explore various aspects of citizenship through an ever-evolving entanglement of agencies. The thesis concludes by arguing that key to the realisation of more just and promising futures and more embracing notions of youth citizenship is the attention paid to relations between belonging, hope and flourishing, which shape, and are shaped by, valences of moral, cultural and sexual citizenship.